Knowledge and management of temporomandibular joint disorders by general dentists in Spain - López-Frías, Francisco-Javier (J Clin Exp Dent, 2019)
BACKGROUND: Given the importance of temporomandibular disorders (TMD), we tried to assess general dentists’ knowledge regarding etiology, diagnosis, and treatment in order to understand their attitude. MATERIAL AND METHODS: A sample of 130 general dentists answered a 16-item questionnaire on three areas – etiology, diagnosis, and management of common temporomandibular disorders – as well as a question on the need for continuous education regarding TMD management in common clinical practice in Spain. Given that the descriptive statistics achieved reflect significantly different values among means in each area, a variance analysis for repeated measurements was applied in order to contrast differences among etiology, diagnosis, and management knowledge levels. RESULTS: The contrast test was based on Wilks’ Lambda, which assumed a value of 0.120 (F = 467.28; p<.001), demonstrating statistically significant differences among knowledge levels in the three dimensions. The effect size for these differences, measured by partial eta squared, was very high (η2p = 0.88). Such parameters were also analyzed to search for potential differences according to professional experience, with differences being exposed as non-significant at the 0.05 level: etiology (T = 1.60; p = 0.113), diagnosis (T = - 0.17; p = 0.868), and treatment (T = 1.10; p = 0.273). CONCLUSIONS: Our study found that, even though clinicians are generally skilled regarding the knowledge of the etiologic that explain the diagnosis of TMD, they have room for improvement in terms of TMD management compared to the other two areas studied. General dentists could benefit from specific educational programs enhancing TMD management skills. Key words:Temporomandibular disorders (TMD), knowledge and management. Clinical competence, postgraduate, continuing professional development. Surveys, education,orofacial pain.